STATIC ANALYSIS OF SHEAR WALLS USING FINITE ELEMENT METHOD - MAHGOUB, ABDELRAHIM MUSA (Universiti Teknologi PETRONAS, 2007)
Shear wall is an important member resisting the lateral forces such as wind and earthquakes forces in the high rise buildings. Different structural models were used for the analysis of shear walls in building. The simplest model for the shear wall is a frame structure using beam/column element. FEM is widely used for analyzing complicated structural systems. The selected structural model must be simple, produce accurate result and be economical. The presence of the opening in shear wall structure further complicated the analysis of this structure and required a special attention. This study covers static structural analysis of solid shear wall as well as shear walls with different opening arrangements. The shear walls were modeled using beam/column and different F.E meshes. The study focuses on the accuracy and effectiveness of different structural models for analyzing shear wall structure. The structural behavior in terms of deformation and stresses distribution are presented and discussed.